Genome−wide expression profile analysis of the NHE and NKA gene family in Rachycentron canadum (Linnaeus, 1766) and its response to salinity adaptation - Chen, Zongfa; Huang, Baosong; Yan, Ziqi; Hong, Yujie; Zhao, Mingming; Jin, Minxuan; Zheng, Anna; Wang, Zhongliang (Frontiers in Marine Science, 2023)
NHE and NKA are important regulators of ion transport in fish and play a pivotal role in maintaining osmotic balance and adapting to salinity changes. However, no systematic identification and functional analysis has been conducted for NHEs and NKAs in the cobia (Rachycentron canadum), a commercially important worldwide flatfish. Herein,12 NHE genes were found to be distributed on 10 chromosomes and 12 NKA genes were found to be distributed on 9 chromosomes were identified in the R. canadum at the genome-wide level. Histopathological examination of the gills demonstrated the response of gill lamellae and chloride cells to salinity, while the microstructure of the intestine and kidney exhibited changes associated with salinity. The findings show that members of the NHE and NKA gene families are widely distributed in gill, brain, and heart tissues. Specifically, NHE genes exhibited high expression levels in the gill, somatic kidney, and brain, whereas NKA genes displayed prominent expression in the gill, brain, and heart. Moreover, salinity adaptation experiments were conducted to examine the response of NHE and NKA genes. In the intestine, NHE1 expression was significantly upregulated following both high and low salt stimulation, while the somatic kidney exhibited a proportional response to changes in salinity. Notably, a significant downward trend in NHE2c expression was observed in the gill, intestine, and somatic kidney with increasing salinity. Following low-salt acclimation, NKAα1b and NKAβ3a were significantly down-regulated in the gill, whereas NKAα3a and NKAβ3a displayed significant up-regulation and down-regulation in the intestine, respectively. In the somatic kidney, NKAα1b, NKAα3a, and NKAβ3a were significantly up-regulated. During high-salt acclimation, the expression patterns of NKAα1b and NKAβ3a in the gill were consistent with those observed during low-salt acclimation, while NKAα3a and NKAβ1b exhibited significant upregulation. Our findings underscore the high conservation of NHE and NKA gene family members in R. canadum and highlight tissue-specific expression patterns and their responses to salinity changes. These results provide valuable insights into the molecular mechanisms governing ion transport and osmoregulation in R. canadum, contributing to the development of novel strategies for enhancing aquaculture practices of this species.